2022
DOI: 10.3390/polym14214586
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Research on the Effect of Temperature on the Properties of Polyurethane Foams

Abstract: Temperature is one of the main factors affecting the properties of polyurethane foams, and there are large differences in the mechanical properties of polyurethane foams at different temperatures. To understand the effect of temperature on the mechanical properties of polyurethane foams and to provide a theoretical basis for the application of polyurethane foams in extreme environments, this paper systematically describes the research on the effect of mold temperature, raw material temperature, and environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 107 publications
1
23
0
Order By: Relevance
“…It also shows that the rising temperatures have influenced the polymer structure of MR foam and its resultant characteristics. Besides, a previous study of basic PU foam has stated that the changed in temperature during service performance have caused changes in the macroscopic properties of the material, such as loss in strength and modulus [30]. The result is in line with a recent study conducted by Rashid et al [21], who found that as the temperature increased from 25 • C to 65 • C, G 0 ′ of MRE has reduced from 0.76 to 0.63 MPa.…”
Section: Strain Sweep Analysis Of Mr Foamsupporting
confidence: 84%
“…It also shows that the rising temperatures have influenced the polymer structure of MR foam and its resultant characteristics. Besides, a previous study of basic PU foam has stated that the changed in temperature during service performance have caused changes in the macroscopic properties of the material, such as loss in strength and modulus [30]. The result is in line with a recent study conducted by Rashid et al [21], who found that as the temperature increased from 25 • C to 65 • C, G 0 ′ of MRE has reduced from 0.76 to 0.63 MPa.…”
Section: Strain Sweep Analysis Of Mr Foamsupporting
confidence: 84%
“…Fish scale powder is composed of collagen fibers, which are known for their high strength, stiffness, and toughness 9 . According to Wang, Zhang 23 polyurethane foam materials generally show a significant reduction in strength as the temperature increases. Previous studies such as Horak, Dvorak 24 and Song, Lu 25 revealed that an increase in temperature caused a loss of strength and modulus.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the improvement of tear resistance under heat aging may be attributable to the presence of collagen fibers and minerals, which could help bridge and distribute stress within the material, preventing the propagation of tears. While temperature conditions can affect material properties, 23 the result suggests that the addition of 1 gram of fish scale powder may help mitigate the negative effects of moisture on tear resistance. The results of this study are consistent with previous research that has investigated the use of natural materials as reinforcements in polyurethane foam composites.…”
Section: Tear Resistance Of Puf-based Compositesmentioning
confidence: 99%
“…For example, the relationship between compressive strength and cell volume or strut size is undefined, although it is well known that smaller cell sizes give a stronger foam. 18,19 X-ray computed microtomography (X-ray μCT) imaging is an alternative non-destructive technique used to characterize foams, allowing precise 3D quantification of internal morphology such as the spatial parameters (cell porosity, cell volume, and cell orientation�ellipticity or anisotropy) and the skeletal parameters (cell strut and wall measurements and the volume of struts). 20−22 This technique has enabled monitoring structural changes in terms of cell parameters during mechanical property testing 23 and modeling thermal properties of various types (metallic/non-metallic) of cellular materials.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, while there are many empirical structure–property relationships, it has not been possible to precisely correlate the 3D structure of RPUF with physical properties to date. For example, the relationship between compressive strength and cell volume or strut size is undefined, although it is well known that smaller cell sizes give a stronger foam. , …”
Section: Introductionmentioning
confidence: 99%